A facile synthesis of some biologically active disperse dyes derived from arylazonicotinates and their application on polyester fabrics - El-Apasery, Morsy Ahmed; Ashkar, Samar Mohamed; Touma, Marwan; Elnagdi, Mohamed Hilmy (European Journal of Chemistry, 2013)
A series of 2-hydroxy- and 2-amino-6-substituted-5-arylazonicotinates monoazo disperse dyes 6 and 8a-d were prepared via condensation of 3-oxo-3-substituted-2-arylhydrazonals 1a-d with active methylene nitriles 2a,b. A high temperature dyeing method was employed to apply these disperse dyes for polyester fabrics. Fastness properties of the dyed samples were measured. Most of the dyed fabrics tested displayed very good fastness level to washing, perspiration and light. Finally, the biological activities of the prepared dyes against gram positive and gram negative bacteria were evaluated.